Bovine viral diarrhoea in cattle: an update. (2nd November 2022) - Paton, Neil; Cooper, Hannah; Griffiths, John; Booth, Richard
Abstract : Gwaredu BVD is the industry led voluntary programme to eradicate bovine viral diarrhoea (BVD) in Wales. This uses check testing to find BVD positive farms and a variety of methods to eradicate the virus on farm. Biosecurity is advised as a follow up to protect the farms. This article discusses why the industry chose to eradicate BVD and why check testing was used. The progress to date, future plans and anticipated challenges are outlined.